Analysis of Tube Design for Clean Water from Stainless Steel 304 and 201 - Muhammad Amin Putro; Prantasi Harmi Tjahjanti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to design the water tube for pure water namely a set of processing tools used to place the water using Autodesk Inventor 2016 software. The data which inputted is stainless steel SS 304 and SS 201, because both of them have the Cr and Ni elements, which will be used as tubes and the top and bottom caps. The results of running data are von mises stress, displacement, and safety factor. The output data were used to obtain the most efficient material and thickness variations between 1.5mm, 2mm, and 3mm. The most suitable and efficient result shown at 3mm thick SS 304 with the maximum value of von mises stress is 14.62 MPa, a maximum displacement of 0.013mm, and a safety factor of 15.